How to manage complex programs : high-impact techniques for handling project workflow, deliverables, and teams - Kendrick, Tom (AMACOM, American Management Association, 2016)
Projects require managers. Programs require maestros. Program manager-it's one of the most challenging jobs you can have. Overseeing and coordinating multiple project teams and thousands of activities may seem a Herculean task, but it's easier with the right tools in hand. Successful program management begins with a good command of project management processes, but these are never sufficient. Once a program exceeds a certain scale, project processes become unwieldy. To see a program successfully through to completion, you must break the work down into simpler, smaller pieces and organize it into interdependent tasks. Complete with diagrams, graphs, and real-life examples, How to Manage Complex Programs explains the ins and outs of program management and provides concrete and effective techniques for structuring deliverables, workflow, and staffing. You'll learn to: Decompose complex deliverables into manageable chunks * Develop coherent plans for component projects * Handle cross-project dependencies * Organize program staff and project leaders into a high-performing team * And more Yes, program management is challenging. But with these proven strategies, it can also be highly rewarding-for you and for your organization.